Application of statistical analysis for identification of climatic tendency - Back, Álvaro José (Pesquisa Agropecuaria Brasileira, 2001)
With the objective to give a statistical treatment in the identification of climatic change and annual tendency, time serie from 1924 to 1998 of rainfall and surface air temperatures for the meteorological station of Urussanga (latitude 28o31' S, longitude 49o19' W and altitude of 48.2 m) was analyzed. The analyses were made through regression analyses and the non-parametric tests of Run, Mann-Kendall and Pettitt. The results indicate warming trends for the mean annual temperature and for January mean temperature, with the change point in 1965. July mean temperature did not present any significant trend. The total annual rainfall and the total rainfall in the fourth trimester of the year presented significant tendency of increasing. For the first three trimesters no significant trend was detected on the total rainfall.